2023
DOI: 10.1038/s41598-023-35430-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of productive performance and fattening efficiency of commercial pigs in China for two consecutive years

Abstract: The purpose of this study: (1) propose an evaluation indicator of the fattening efficiency of commercial pigs (Yorkshire × Landrace × Duroc)—fattening efficiency index (FEI). (2) Analyze the correlation to find the main productive factors affecting the FEI. (3) Compare and analyze the yearly/monthly/different piglets’ sources of productive performance in 2020 and 2021. The data included 2592 commercial pig batches in 2020 and 3266 in 2021, with a total of 6,134,234 commercial pigs. Descriptive statistics and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was revealed that consumers' overall top three motives to buy and eat pork were the quality, price, and taste [20]. The productivity of pig farms depends on several factors: breeds, housing technology, the rotation of finisher barns influenced by day feed-in, time of empty, finishers' ADG, feed conversion ratio, and, finally, abattoirs' pricing of slaughter animals [21]. There is a high demand for high-quality and equivalent carcasses from meat processors and consumers throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that consumers' overall top three motives to buy and eat pork were the quality, price, and taste [20]. The productivity of pig farms depends on several factors: breeds, housing technology, the rotation of finisher barns influenced by day feed-in, time of empty, finishers' ADG, feed conversion ratio, and, finally, abattoirs' pricing of slaughter animals [21]. There is a high demand for high-quality and equivalent carcasses from meat processors and consumers throughout the year.…”
Section: Discussionmentioning
confidence: 99%